BRIDGING LITERATURE AND CINEMA A STUDY OF A SUITABLE BOY AS NOVEL AND WEB SERIES - Bharatsinh, Zala Krupaba; Rangani, Devang (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper delves into the adaptation of Vikram Seth’s novel A Suitable Boy into a web series directed by Mira Nair, exploring the intersection of literature and cinema. By analyzing both the novel and its screen adaptation, the paper investigates how key themes such as tradition versus modernity, religious tensions, and personal versus political dilemmas are translated from text to screen. The study looks at the difficulties of reducing a 1,300-page book to a six-part television series, emphasising characterisation, narrative structure, and theme representation. It also covers the wider trend of novel-to-web-series adaptations in the digital age, highlighting the influence of streaming services on modern narrative. Ultimately, the paper aims to assess how Nair’s visual interpretation opposes and enhances Seth’s literary vision, taking into account the wider effects of serialised novel adaptations.